Effects of short-term grazing exclusion on plant phenology and reproductive succession in a Tibetan alpine meadow - Zhu, Juntao (Sci Rep, 2016)
Grazing exclusion (GE) has been widely considered as an effective avenue for restoring degraded grasslands throughout the world. GE, via modifying abiotic and biotic environments, inevitably affects phenological development. A five-year manipulative experiment was conducted in a Tibetan alpine meadow to examine the effects of GE on phenological processes and reproductive success. The study indicated that GE strongly affected phenological development of alpine plant species. Specifically, the low-growing, shallow-rooted species (LSS), such as Kobresia pygmaea, are more sensitive to GE-caused changes on upper-soil moisture and light. GE advanced each phonological process of K. pygmaea, except in the case of the treatment of fencing for 5 years (F5), which postponed the reproductive stage and lowered the reproductive success of K. pygmaea. Increased soil moisture triggered by GE, especially in the upper soil, may stimulate growth of LSS. However, the thick litter layer under the F5 treatment can influence the photoperiod of LSS, resulting in suppression of its reproductive development. These findings indicate that plant traits associated with resource acquisition, such as rooting depth and plant height, mediate plant phenology and reproductive responses to grazing exclusion treatments.